Enforceability of knock-for-knock indemnities in oilfield service contracts in Thailand - Wan Zahari, Wan Mohd Zulhafiz; Md. Radzi, Mohd Shahril Nizam (National Institute of Development Administration (NIDA), 2016)
This research addresses the issue of enforceability of mutual indemnity and hold harmless clauses (MIHH) pertaining to bodily injury and death in oilfield service contracts in Thailand. Thai Unfair Contract Terms Act B.E. 2540 (A.D. 1997) (“TUCTA”) prohibits a contracting party to restrict or exclude liabilities pertaining to bodily injury and death arising from his negligence. This restriction might be thought to have an effect of hampering the risk allocation. Similar restriction contains under the Unfair Contract Terms Act 1977 (“UCTA”). However, by virtue of the Supreme Court decision in Farstad Supply A/S VS Enviroco Ltd [2011] UKSC 16, the MIHH could be enforceable despite the restriction. Nevertheless, the IMHH will be subject to the reasonableness test under UCTA. Thus, it could be argued that in spite of the restriction under TUCTA, the IMHH in standard form oilfield service contracts e.g., LOGIC could still be enforceable in Thailand, subject to certain limitations.